2015
DOI: 10.1002/elsc.201500030
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pig manure liquid digestate in horizontal flow constructed wetlands: Effect of aeration

Abstract: With the rapid development of scaled anaerobic digestion of pig manure, the generation of liquid anaerobic digestate exceeds the farmland loading capacity, causing serious environmental pollution. Three laboratory‐scale horizontal subsurface flow constructed wetlands (CWs; planted + aeration, planted, and unplanted) were set up to investigate the feasibility of liquid digestate treatment in wetlands. Treatment capacity in different wetlands was evaluated under different influent concentrations (chemical oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
(60 reference statements)
2
10
0
Order By: Relevance
“…Biochemical oxygen demand (BOD) values were approximated using the ratio COD/BOD = 2 in the studies where BOD was not reported (Ouellet-Plamondon et al 2006 ; Fan et al 2013c ; Zhong et al 2015 ; Zapater-Pereyra et al 2015 ; Uggetti et al 2016 ). (1) Ouellet-Plamondon et al ( 2006 ), (2) Nivala et al ( 2007 ), (3) Zhang et al ( 2010 ), (4) Fan et al ( 2013c ), (5) Butterworth et al ( 2013 ), (6) Zapater-Pereyra et al ( 2014 ), (7) Li et al ( 2014 ), (8) Zhong et al ( 2015 ), (9) Uggetti et al ( 2016 ), (10) S. Wu et al ( 2016b ), (11) Ye and Li ( 2009 ), (12) Zapater-Pereyra et al ( 2014 ), (13) Zapater-Pereyra et al ( 2015 ) AA artificial aeration, HFCW horizontal flow constructed wetland, HCW hybrid constructed wetland, WT wastewater type, FF fish farm, LL landfill leachate, D domestic, S synthetic, P piggery, HLR hydraulic loading rate, OLR organic loading rate, AM aeration mode, CA continuous aeration, IA intermittent aeration, AP aeration position, B bottom, M middle, S surface, F front, R rear, AFR airflow rate, DO dissolved oxygen, TSSs total suspended solids, COD chemical oxygen demand, NH 4 + -N ammonium-nitrogen, TN total nitrogen, TP total phosphorus, NA not available, H + F + H HFCW free water surface flow CW and HFCW in a stack design, H + H HFCW and horizontal flow filter connected in series, V + H VFCW over horizontal flow filter…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical oxygen demand (BOD) values were approximated using the ratio COD/BOD = 2 in the studies where BOD was not reported (Ouellet-Plamondon et al 2006 ; Fan et al 2013c ; Zhong et al 2015 ; Zapater-Pereyra et al 2015 ; Uggetti et al 2016 ). (1) Ouellet-Plamondon et al ( 2006 ), (2) Nivala et al ( 2007 ), (3) Zhang et al ( 2010 ), (4) Fan et al ( 2013c ), (5) Butterworth et al ( 2013 ), (6) Zapater-Pereyra et al ( 2014 ), (7) Li et al ( 2014 ), (8) Zhong et al ( 2015 ), (9) Uggetti et al ( 2016 ), (10) S. Wu et al ( 2016b ), (11) Ye and Li ( 2009 ), (12) Zapater-Pereyra et al ( 2014 ), (13) Zapater-Pereyra et al ( 2015 ) AA artificial aeration, HFCW horizontal flow constructed wetland, HCW hybrid constructed wetland, WT wastewater type, FF fish farm, LL landfill leachate, D domestic, S synthetic, P piggery, HLR hydraulic loading rate, OLR organic loading rate, AM aeration mode, CA continuous aeration, IA intermittent aeration, AP aeration position, B bottom, M middle, S surface, F front, R rear, AFR airflow rate, DO dissolved oxygen, TSSs total suspended solids, COD chemical oxygen demand, NH 4 + -N ammonium-nitrogen, TN total nitrogen, TP total phosphorus, NA not available, H + F + H HFCW free water surface flow CW and HFCW in a stack design, H + H HFCW and horizontal flow filter connected in series, V + H VFCW over horizontal flow filter…”
Section: Resultsmentioning
confidence: 99%
“…Biochemical oxygen demand (BOD) values were approximated using the ratio COD/BOD = 2 in the studies where BOD was not reported (Ouellet-Plamondon et al 2006 ; Fan et al 2013c ; Zhong et al 2015 ; Zapater-Pereyra et al 2015 ; Uggetti et al 2016 ). (1) Ouellet-Plamondon et al ( 2006 ), (2) Nivala et al ( 2007 ), (3) Zhang et al ( 2010 ), (4) Fan et al ( 2013c ), (5) Butterworth et al ( 2013 ), (6) Zapater-Pereyra et al ( 2014 ), (7) Li et al ( 2014 ), (8) Zhong et al ( 2015 ), (9) Uggetti et al ( 2016 ), (10) S. Wu et al ( 2016b ), (11) Ye and Li ( 2009 ), (12) Zapater-Pereyra et al ( 2014 ), (13) Zapater-Pereyra et al ( 2015 )…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the high NH 4 + -N and salinity content may compromise the plant survival in CWs [26]. In several papers, the digestate liquid fraction (DLF) was diluted (from 1:2 to 1:20 DLF:water) before CW treatment, and in some cases it was additionally subjected to a residence time in a sediment tank [13,19,20,31] with the aim to reduce the suspended solids and NH 4 + -N concentration. However, dilution may not be considered a suitable solution in practical conditions because it implies higher volumes to store and manage.…”
Section: Introductionmentioning
confidence: 99%
“…Among all energy sources, the use of energy from biogas produced by anaerobic digestion (AD) plants is encouraged both by their availability and by the strong economic subsidies . Therefore, AD of manure from stables, crop residues, wastes from food industry, municipal wastes, and dedicated energy crops is becoming increasingly popular worldwide . Thus, the increasing number of AD plants (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…As concerns the biological methods, available processes for liquid digestate treatments are conventional process with nitrification/denitrification and advanced biological processes such as nitritation‐denitritation process and completely autotrophic process (partial nitritation and Anammox process) . Recently, interesting results were obtained by the application of constructed wetlands with intermittent aeration on the enhanced removal of organic matter and nitrogen .…”
Section: Introductionmentioning
confidence: 99%